Research and Fabrication of an Antenna Based on Meta-materials with Negative Refractive Index - Thuy, Dang Thi Thanh (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract: For fast developing materials science, the communication technology also introduces new applications especially in the field of application of new materials and devices. Meta-materials with repeating structures that exhibit the negative refractive index, negative dielectric constant, and negative magnetic permeability promise many benefits in the wireless communication using a new class of microwave antennas. These novel antennas overcome disadvantages of traditional microwave antennas while having smaller physical size, wider band-width and higher efficiency. In this paper we present the results of fabrication and test of meta-structured antennas. Keywords: Meta-material, antenna, meta-antenna, negative refractive index…